Advanced Vehicle Tracking System Using ARM7 - Kishore, L.; Raja, Arun (Asian Journal of Electrical Sciences, 2015)
To Track the position of the vehicle by means of GPS device and automatically sending the data to the remote server webpage and display the current position of the device in the Google map to the authorities. In institution or in ATM cash filling vehicle, most of the time we need to monitor position or path vehicle whether it’s moving in correct direction or not. This system used the ARM7 controller. The real time vehicle tracking and monitoring system tracks the vehicle and displays the current location of the vehicle in the remote server using Google maps. It has the ability to communicate over the remote areas where user needs the current location of vehicle. It can provide Tele-monitoring system for inter-cities transportation vehicles such as taxis and buses. This system is integrated with GPS and GSM to provide features like Location information and Real time tracking using SMS.